Women Empowerment in Bekasi City Turning Catfish into Frozen Food - Indriyanto, Irwan; Paramitra, Yuaniko; Syarif Hartawan, Muhammad; Laila, Zulfa; Hidayatullah, Ridho (Unram Journal of Community Service, 2025)
The position of women as family financial managers is emphasized from a series of productive efforts that strategically utilize the potential of social capital in the socio-community environment The purpose of the community service activity is to implement a series of activities that will have beneficial value to strengthen the knowledge and skills capacity of the Bina Karya Srikandi housewife group to be able to utilize the results of the residents' catfish harvest into a variety of frozen food by utilizing technology in the production and marketing process. The form of community service that the author uses in this activity divided into two, namely, Training Method and Provision of catfish product processing equipment. Training that provided in this activity focuses on 3 areas, namely partner HR development, product development and marketing process development, the development carried out is an effort by the author to help overcome the problems experienced by partners. The results of the activity is we develop our partner in 3 areas such as, HR development, Product and marketing development, we providing training on processing catfish meat into frozen food made from catfish, such as catfish meatballs, ready-to-fry catfish, and catfish otak otak to increase their awareness about their brand image and engagement with social media marketing by provide social media Instagram for Bina Karya Srikandi to promote their product. We also help them create brand logo. Bina Karya Srikandi now have more variant catfish product and more marketing channel.